Assessment of cytological and biochemical parameters stability in cerebrospinal fluid - Renan Domingues (Jornal Brasileiro de Patologia e Medicina Laboratorial, 2019)
Objective: The aim of this study was to evaluate the stability, in 12 hours, of cytological and biochemical parameters of the cerebrospinal fluid (CSF). Methods: Cerebrospinal fluid (CSF) samples were aliquoted into five different tubes and stored at room temperature. The first aliquot was immediately analyzed and the others analyzed after 2, 4, 6 and 12 hours. For cytological analysis, samples of at least 20 leukocytes/mm3 were included. Analysis of variance of the results and the comparison of the clinical interpretation of the results at the different times were performed. Results: There was no significant decrease in the number of leukocytes and erythrocytes by the analysis of variance (ANOVA). The clinical interpretation of the cytology did not result in different results in any of the evaluated times. There was no significant variation in the biochemical parameters. Conclusion: The results suggest that the storage of CSF samples for 12 hours at room temperature does not significantly compromise clinical interpretation. Future studies are still required in order to evaluate the behavior of these parameters in samples of cell counts closer to boundered values.